A Comparative Study of Percutaneous Aspiration vs. Incisional Drainage for the Management of Breast Abscess - Muhammad Hamayun Khan, Iram Bashir, Aftab Alam, Ali Raza, Aftab Hussain, Aziz Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breast abscess is a common condition that primarily affects lactating women but can also occur in non-lactating females and males. The management of breast abscesses typically involves two major approaches: percutaneous aspiration and incisional drainage. This study aims to compare the outcomes of these two methods in the treatment of breast abscesses. Objective: To evaluate the effectiveness, recovery time, complication rates, and patient satisfaction of percutaneous aspiration versus incisional drainage in the management of breast abscesses in 120 patients. Methods: A comparative/prospective study was conducted on 120 patients diagnosed with breast abscesses at Department of surgery DHQ / Mufti Mehmood Teaching hospital and Gomal Medical college Dera ismail khan. The patients were randomly divided into two groups: 60 patients underwent percutaneous aspiration, and 60 patients underwent incisional drainage. The primary outcomes measured were resolution of the abscess, complication rates, and patient satisfaction. Results: Both treatments showed high rates of abscess resolution. Percutaneous aspiration demonstrated a higher success rate in small abscesses (85%), whereas incisional drainage was more effective for larger abscesses (92%). The average recovery time was shorter for percutaneous aspiration (5 days) compared to incisional drainage (10 days). Complications such as recurrence and infection were more common in the incisional drainage group (8%) compared to the percutaneous aspiration group (3%). Conclusion: Percutaneous aspiration is an effective and less invasive option for the management of breast abscesses, especially for smaller abscesses. Incisional drainage remains a preferred option for larger and complicated abscesses. Keywords: Breast abscess, percutaneous aspiration, incisional drainage, treatment outcomes, complications, patient satisfaction.